2012
DOI: 10.1021/ac301853q
|View full text |Cite
|
Sign up to set email alerts
|

Time-of-Flight Secondary Ion Mass Spectrometry-Based Molecular Distribution Distinguishing Healthy and Osteoarthritic Human Cartilage

Abstract: ABSTRACT. Osteoarthritis (OA) is a pathology that ultimately causes joint destruction.The cartilage is one of the principal affected tissues. Alterations in the lipid mediators and an imbalance in the metabolism of cells that form the cartilage (chondrocytes), have been described as contributors to the OA development. In this study, we have studied the distribution of lipids and chemical elements in healthy and OA human cartilage. Time of flight secondary ion mass spectrometry (TOF-SIMS) allows us to study the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
80
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(84 citation statements)
references
References 41 publications
4
80
0
Order By: Relevance
“…In a pioneering study conducted by Lipiello and colleagues, elevated FA levels were observed in osteoarthritic articular cartilage, and were positively associated with histological severity (25). More recently, Cillero-Pastor also reported significant FA accumulation in the surface of OA articular cartilage using mass spectrometry (32). Chondrocytes can synthetize and accumulate endogenous lipids and also are able to internalize exogenous FA and store them in lipid droplets (33).…”
Section: Discussionmentioning
confidence: 94%
“…In a pioneering study conducted by Lipiello and colleagues, elevated FA levels were observed in osteoarthritic articular cartilage, and were positively associated with histological severity (25). More recently, Cillero-Pastor also reported significant FA accumulation in the surface of OA articular cartilage using mass spectrometry (32). Chondrocytes can synthetize and accumulate endogenous lipids and also are able to internalize exogenous FA and store them in lipid droplets (33).…”
Section: Discussionmentioning
confidence: 94%
“…MSI techniques have only recently been implemented in cartilage research. One study employed a time of flight secondary ion mass spectrometry (TOF-SIMS) workflow in order to acquire molecular-specific spatial distribution of lipids in normal and OA cartilage [8]. A further study used MALDI-MSI to identify and study OA specific peptides and proteins in cartilage [9].…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14] SIMS may be dynamic or static: while dynamic SIMS can analyze only secondary atomic or diatomic ions, static SIMS uses pulsed ions and thereby enables the analysis of organic molecules. [15] In particular, high mass molecules can be analyzed with high sensitivity when cluster ion technology is used.…”
mentioning
confidence: 99%